Animal Biotechnology and Intellectual Property Rights: A Comprehensive Analysis - P, Das; S, Bandyopadhyay (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Animal biotechnology can be defined as the collection of methods employed for altering animals in order to serve different uses such as in the farming systems, laboratory and in the treatment of diseases among others. This field has come a long way and new accomplishments have been witnessed in such fields as genetic engineering, cloning and production of transgenic animals. Nevertheless, such enhancements also present related issues with regard to intellectual property rights as well. Taking the subjects of animal biotechnology with IPR, ethical, legal, and economical aspects into consideration. This paper gives a description of the developments made in the course of the animal biotechnology, analyses the existing legal regulation of IPR in this area and examines the main problems and barriers.